(untitled) - Earle, Alan C. (Logan, Utah, 1978)
Farmers water management constraints to full crop procution were investigated by an integrated inter-disciplinary survey technique and delineated into four ategories, physical and irrigation, agonomic and economic, knownledge and information and organizational and institutional services received by farmers.
Keywords: Irrigation,Water conservation